Публічна безпека в класичній давньогрецькій політико-правовій думці (вчення Сократа, Платона, Аристотеля) - Загуменна, Ю. О.; Zagumenna, Yu. O.; Юлія Загуменна (Sciencerise: juridical science. – 2021. – № 4 (18). – С. 15-22, 2021)
Проведено теоретико-правовий аналіз ключових особливостей загальнофілософського та спеціально-правового розуміння й тлумачення проблем безпеки людини, суспільства та держави в історії політико-правових учень античної доби. Показано, що давньогрецька політико-правова думка демонструє широку панораму оригінальних поглядів на проблематику становлення, розвитку, функціонування та гарантування публічної та особистої, внутрішньої та зовнішньої, воєнної та міжнародної, політичної та економічної безпеки в контексті політико-правових концепцій, які відображали складну діалектику співвідношенням і взаємодії індивіда, суспільства, права та держави. З’ясовано, що в давньогрецькій політико-правовій думці порушуються та по-різному вирішуються питання щодо сутності публічної безпеки.

The aim of the article is to carry out the theoretical and legal analysis of key features of general philosophical and special legal understanding and interpretation of human, social and state security problems in the history of political and legal scholars of ancient times, in particular on the basis of scientific research of ancient Greek authors, opinions of that period, against the background of widespread collective ideas about security as a state of social relations, the condition of human (social) life and/or a kind of social value, objects (spheres) of this security, as well as subjects and regulatory mechanisms to ensure the appropriate state of society and the state. It is shown, that the ancient Greek political and legal thought demonstrates a wide panorama of original views on the formation, development, functioning and guarantee of public and personal, internal and external, military and international, political and economic security in the context of political and legal concepts that reflect complex dialectics. and the interaction of the individual, society, law and the state. It has been found, that the ancient Greek political and legal thought raises questions about the essence of public security. The matter of public security is an essential function of the state, which is realized by it both in the external sphere (military and foreign political security) and within the country (internal or domestic political security). Developed at the theoretical and philosophical level, the idea of good governance (Democritus, Plato, Aristotle, Polybius) is the idea of guaranteeing its security: bad governance - the key to the decline and collapse of the state, the death of its citizens. The philosophical concepts of Socrates, Plato and Aristotle are the most fundamental for the further development of political and legal models of public security.

Проведен теоретико-правовой анализ ключевых особенностей общефилософского и специально-правового понимания и толкования проблем безопасности человека, общества и государства в истории политико-правовых учений античных времен. Показано, что древнегреческое политико-правовое мнение демонстрирует широкую панораму оригинальных взглядов на проблематику становления, развития, функционирования и обеспечения публичной и личной, внутренней и внешней, военной и международной, политической и экономической безопасности в контексте политико-правовых концепций, отражающих сложную диалектику соотношением и взаимодействия индивида, общества, права и государства. Выяснено, что в древнегреческом политико-правовом учении поднимаются и по-разному решаются вопросы сущности публичной безопасности.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Історія. History. История; політико-правова думка; political and legal opinion; политико-правовая мысль; антична доба; ancient times; античность; Стародавня Греція; Ancient Greece; Древняя Греция; право; law; військово-політична могутність; military and political power; военно-политическое могущество; публічна безпека; public safety; публичная безопасность